Panniculitis: rheumatological aspects - O. N. Egorova; B. S. Belov (Современная ревматология)
Different types of panniculitis (Pn) can be one of the symptoms of rheumatic diseases (RDs). Pn is a group of heterogeneous inflammatory diseases that are characterized by subcutaneous adipose tissue (SAT) lesion and often occur with musculoskeletal and visceral involvements. There is no single concept of the etiology and pathogenesis of Pn. Infections, injures, hormonal and immune disorders, drug intake, pancreatic disease, malignant neoplasms, etc. can play a role in the development of Pn. The latter is associated with RDs in a fairly large group of patients. There have recently been reports of about 200 and 50 cases of only idiopathic lobular Pn in the world and Russian literature, respectively. There have also been publications on other types of Pn, such as erythema nodosum, eosinophilic fasciitis, superficial migratory thrombophlebitis, lupus Pn, dermatomyositis Pn, scleroderma systematica, gout, psoriatic arthritis, etc. There is now a need to study skin changes and SAT lesions in the context of RDs, which will be able to estimate the true clinical and prognostic value of Pn in RDs. Based on recent literature data, this review characterizes the main types of Pn, their clinical and histological signs, and diagnostic methods.